Effect of different production types on the yield and ß-carotene content of sweet potato /cultivar Ásotthalmi- 12/ - Balázs, Viktor; Helyes, Lajos; Pék, Zoltán; Neményi, András; Takács, Sándor; Égei, Márton; Daood, Hussein G. (Acta Agraria Debreceniensis, 2021)
Production of sweet potato is extending in Hungary, despite the fact that there is no field-specific production technology. Therefore, many growers cannot utilize potential yields and quality. The goal of this study was to determine the optimal production method of the Ásotthalmi 12, a Hungarian sweet potato cultivar which can adapt to the Hungarian climate. The effect of single and twin rows production on the yield of this cultivar was examined. The planting was carried out on June 24th, the harvesting on October 20th and the growing-season was 120 days long. Uniform nutrient supply was applied to the whole field experiment. During basic fertilization, 206 kg Knd 20 kg N, 36 kg P ha-1 were used on the soil. While forming the ridges, we used an additional 25 kg N, 45 kg P and 62.5 kg K ha-1. We adopted drip tape irrigation on the experimental field. After the planting, from the 8th week of the vegetation, another 21 kg ha-1 K, 10 kg ha-1 MgSO4, and 2 kg ha-1 Ca(NO3)2 was added in one dosage weekly, until the 13th week of vegetation. At the evaluation of the experiment, we examined the yield regarding the whole experimental plot. SPAD and fluorescence measurements were carried out on 08.16. 2019, 08.28.2019, and on 09.13.2019, during the watering break. To demonstrate the difference between the dates, we applied ANOVA and Tukey post-hoc tests. For the measurement of phytonutrients HPLC, a liquid chromatograph was used, where the carotenoid content of the Ásotthalmi 12 cultivar was determined in connection with the different production methods. Test results showed that twin rows production leads to a nearly 30% greater yield, than single row production. We determined, that the growth of yield correlates negatively to the ß-carotene content of the Ásotthalmi 12 cultivar sweet potato.